The Influence of Career Development and Work Environment on Performance Non-permanent PNS Education Staff and Retention As an intervening variable in the Hasanuddin University - Nurul Pratiwi; Mahlia Muis; Yunus Amar (Hasanuddin Journal of Business Strategy, 2020)
This study is aimed to know the influence of development career and work environment and retention as an intervening variable on the performance of non-permanent civil service (Non-PNS) assigned as educational staff at the Hasanuddin University (Unhas). The research was a quantitative descriptive study with the use of the staff of Non-Permanent Civil Servant Education, called Tendik as respondents, that have been working for 5 to 10 years. Methods of data collection were used through the distribution of questionnaires which is tested the validity and reliability of all items evaluated afterward. Data analysis was performed using Statistical Product and Service Solution (SPSS) version 25 and analysed using path analysis. To evaluate the indirect effect between variables, the study applied the Sobel Test. The result of this study indicates that career development and the work environment have a significant effect on retention. To the second equation evaluated, the retention has a significant effect on performance. Interestingly, career development and the work environment have no significant effect on performance. The career development and the work environment have a significant effect on the performance through retention as an intervening variable.